Association of immune‐mediated necrotizing myopathy with HLA polymorphisms. (15th January 2023) - Ohnuki, Yuko; Suzuki, Shigeaki; Uruha, Akinori; Oyama, Munenori; Suzuki, Shingo; Kulski, Jerzy K.; Nishino, Ichizo; Shiina, Takashi
Abstract : Immune‐mediated necrotizing myopathy (IMNM) is a type of autoimmune myositis typically characterized clinically by proximal muscle weakness with elevated creatine kinase levels, pathologically by myofiber necrosis and regeneration with paucity of lymphocytic cell infiltration, and serologically by the presence of either of two myositis‐specific autoantibodies, anti‐SRP, and anti‐HMGCR antibodies. However, the HLA loci and alleles associated with IMNM are still not fully understood at least partly because IMNM was a relatively recently established condition. In this study, we genotyped the six HLA loci (HLA‐A, ‐B, ‐C, ‐DRB1, ‐DQB1 and ‐DPB1) in 250 patients (237 patients over age 18 years and 13 juvenile patients) diagnosed with IMNM based on clinicopathological features and autoantibody information and performed a case control study with Japanese healthy subjects. In the adult patients, specific HLA alleles associated with IMNM were identified at all HLA loci, with DRB1*08:03 showing the strongest association (OR = 2.5; p = 0.00000017). Furthermore, subgroup analysis with various clinical information showed that C*03:04 (OR = 3.7; p = 0.00012) was a higher risk allele for collagen disease in adult patients, and B*13:01 (OR = 23.2; p = 0.021) and C*03:04 (OR = 5.8; p = 0.0074) were higher risk for juvenile patients with anti‐HMGCR antibody‐positive IMNM. These findings will help to better understand the HLA genetic background and features of IMNM in designing future studies.